STORM WAVE MODELING AND IT'S VALIDATION BY THE MODERN WAVE MEASUREMENT DEVICES - Hung, Nguyen Manh; Dien, Duong Cong (Vietnam Journal of Marine Science and Technology, 2008)
The  storm  wave  is  a  marine  hydro  dynamical  parameter  which is  very serious,  especially for the marine constructions which often withstand all the severe weathers in  the sea.  The  East Sea is suffered from  one of five storm generation regions in  the world that explain why the storm wave modeling is an important task of the researchers.  in the paper,  the storm wave modeling has been presented.  The  main focus has been paid in the calibration and verification procedure using the modern types of wave measurement, among them the satellite wave  measurements  are  the  most optimistic.  The  results  of validation  show  that  the  storm wave modeling is sufficient for the marine construction design and activities.